Impact of 6-month triptorelin formulation on predicted adult height and basal gonadotropin levels in patients with central precocious puberty - Yoo, Eunjoo; Kim, Sinae; Jung, Hye Lim; Shim, Jung Yeon; Shim, Jae Won; Kim, Deok Soo; Kwak, Ji Hee; Kim, Eun Sil; Yang, Aram (Frontiers in Endocrinology, 2023)
Background: Triptorelin, a long-acting gonadotropin-releasing hormone (GnRH) agonist, is available in 1-, 3-, and 6-month formulations to treat central precocious puberty (CPP). The triptorelin pamoate 22.5-mg 6-month formulation recently approved for CPP offers greater convenience to children by reducing the injection frequency. However, worldwide research on using the 6-month formulation to treat CPP is scarce. This study aimed to determine the impact of the 6-month formulation on predicted adult height (PAH), changes in gonadotropin levels, and related variables. Methods: We included 42 patients (33 girls and nine boys) with idiopathic CPP treated with a 6-month triptorelin (6-mo TP) formulation for over 12 months. Auxological parameters, including chronological age, bone age, height (cm and standard deviation score [SDS]), weight (kg and SDS), target height (TH), and Tanner stage, were evaluated at baseline, and after 6, 12, and 18 months of treatment. Hormonal parameters, including serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), and estradiol for girls or testosterone for boys, were analyzed concurrently. Results: The mean age at treatment initiation was 8.6 ± 0.83 (8.3 ± 0.62 for girls, 9.6 ± 0.68 for boys). The peak LH level following intravenous GnRH stimulation at diagnosis was 15.47 ± 9.94 IU/L. No progression of the modified Tanner stage was observed during treatment. Compared to baseline, LH, FSH, estradiol, and testosterone were significantly reduced. In particular, the basal LH levels were well suppressed to less than l.0 IU/L, and the LH/FSH ratio was less than 0.66. The bone age/chronological age ratio remained stable with a decreasing trend (1.15 at the start of treatment, 1.13 at 12 months, 1.11 at 18 months). PAH SDS increased during treatment (0.77 ± 0.79 at baseline, 0.87 ± 0.84 at the start of treatment, 1.01 ± 0.93 at six months, and 0.91 ± 0.79 at 12 months). No adverse effects were observed during treatment. Conclusion: The 6-mo TP suppressed the pituitary-gonadal axis stably and improved the PAH during treatment. Considering its convenience and effectiveness, a significant shift to long-acting formulations can be expected.